Recruitment problems: a survey of senior dental students' attitudes towards junior jobs in maxillofacial surgery. Issue 1 (January 2022) - Geddes, A.; White, L.
Abstract: Recruitment to specialist training in all 10 surgical specialities has been in decline in recent years. There have, in recent years, been perceived difficulties in recruiting dentists into DCT or SHO roles in Maxillofacial Surgery units with posts going unfilled. This survey examines the reasons behind this recruitment issue.